Characterization of Alnus acuminata (Kunth) in a silvopastoral arrangement in the high Andean region of Colombia - Obando-Enriquez, Bayron Giovanny (2023)
Silvopastoral systems are used in livestock in Andean milk basins. Alnus acuminata (Kunth) is one of the forestry species employed for their benefits in this kind of productive models. With the objective of providing knowledge about the specie, in the AGROSAVIA Obonuco’s Research Center located in the municipality of Pasto (Nariño, Colombia) 26 individuals of A. acuminata aged 22 years established in scattered trees were evaluated. Seven dasometric variables, 14 morphological descriptors, opacity and light intensity in two environments (direct sunlight and under canopy) were included in the study. In the individuals of A. acuminata average values were recorded in total height of 11.74 m and in DBH of 19.17 cm, with crown dimensions in height of 2.3 m, size of 9.5 m, diameter of 7.61 m and area of 49.69 m2. Regarding to architecture, they exhibited predominant semicircular shape (65.38%), cylindrical stem (96.15%) with some curvatures (57.69%), erect branching (84.62%), without branching and few bifurcations (96.15%). The leaf area index in the six-month period ranges from 0.72 to 4.09 with opacity between 58.56% and 85.95%. At direct sunlight the light intensity was between 23850 and 40750 lux. To generate information about the development and the characteristics of A. acuminata, will provide bases to agroforestry and livestock development with greater productivity and scientific rigor.